Inhibition of heart mitochondrial lipid peroxidation by non-toxic concentrations of carvedilol and its analog BM-910228 - Santos, Dario J. S. L. (2001)
Carvedilol, a non-selective [beta]-adrenoreceptor blocker, has been shown to possess a high degree of cardioprotection in experimental models of myocardial damage. Reactive oxygen species have been proposed to be implicated in such situations, and antioxidants have been demonstrated to provide partial protection to the reported damage. The purpose of our study was to investigate the antioxidant effect of carvedilol and its metabolite BM-910228 by measuring the extent of lipid peroxidation in a model of severe oxidative damage induced by ADP/FeSO4 in isolated rat heart mitochondria. Carvedilol and BM-910228 inhibited the thiobarbituric acid-reactive substance formation and oxygen consumption associated with lipid peroxidation with 50 values of 6 and 0.22 [mu]M, respectively. Under the same conditions, the 50 values of [alpha]-tocopheryl succinate and Trolox were 125 and 31 [mu]M, respectively. As expected, the presence of carvedilol and BM-910228 preserved the structural and functional integrity of mitochondria under oxidative stress conditions for the same concentration range shown to inhibit lipid peroxidation, since they prevented the collapse of the mitochondrial membrane potential ([Delta][Psi]) induced by ADP/FeSO4 in respiring mitochondria. It should be stressed that neither carvedilol nor BM-910228 induced any toxic effect on mitochondrial function in the concentration range of the compounds that inhibits the peroxidation of mitochondrial membranes. In conclusion, the antioxidant properties of carvedilol may contribute to the cardioprotective effects of the compound, namely through the preservation of mitochondrial functions whose importance in myocardial dysfunction is clearly documented. Additionally, its hydroxylated analog BM-910220, with its notably superior antioxidant activity, may significantly contribute to the therapeutic effects of carvedilol.